Health-related quality of life (EQ-5D + C) among people living in artisanal and small scale gold mining areas in Zimbabwe: a cross-sectional study - Butscher, Friederike-Marie; Rakete, Stefan; Tobollik, Myriam; Mambrey, Viola; Moyo, Dingani; Shoko, Dennis; Muteti-Fana, Shamiso; Steckling-Muschack, Nadine; Bose-O’Reilly, Stephan (BioMed Central Ltd, 2021)
Background: In Zimbabwe, an estimated 500,000 people work in the sector of artisanal and small-scale gold mining (ASGM). Two million Zimbabweans are dependent on this sector. Using mercury is common to extract gold from ore. Long term exposure to mercury can cause various adverse health conditions including chronic mercury intoxication. The influence of these adverse health effects on the health-related quality of life (HRQoL) is still unknown. The aim of this study is to assess the HRQoL of people who identify themselves as miners, and to analyze potential influencing factors, such as age, years of working with mercury and health conditions caused by mercury exposure. Methods: This cross-sectional study assessed the HRQoL using the standardized EQ-5D + C (3 L) questionnaire and collected human specimens (blood, urine) of people living and possibly working in ASGM areas in Zimbabwe. Factors such as age, years of working with mercury and adverse health conditions possibly caused by mercury exposure were analyzed with regards to their influence on the HRQoL. Results: The 207 participants (82% male, mean age 38 years) reported 40 different health states. Of the study participants 42.5% reported to be in complete good health while 57.5% reported being unwell in different ways. Nine participants (4.3%) were identified with chronic mercury intoxication, whereas 92 participants (33.3%) had mercury levels above the “Alert” threshold in at least one specimen. Having chronic mercury intoxication has a significant negative influence on the HRQoL, when taking into account age, gender and years of working with mercury. Cognitive problems were the most reported in the questionnaire, however, the association between this domain separately and the HRQoL was not verified. Conclusion: This study shows that adverse health effects caused by chronic exposure to mercury, have a negative influence on the HRQoL among people living in ASGM areas.